The effects of syntactic maturity and syntactic complexity on reading comprehension: An empirical test of Smith's psycholinguistic theory of reading - Manning, Andrew R (University of Ottawa (Canada), 1977)
Abstract not available.
Keywords: Education, Educational Psychology.; Education, Reading.